PSVII-4 Ruminal fermentation and enteric methane production of legumes containing condensed tannins fed in continuous culture. (5th December 2019) - Soder, Kathy J; Roca-Fernandez, Ana; Dillard, S Leanne
Abstract: A continuous culture fermentor study was conducted to assess nutrient digestibility, VFA concentration, microbial protein synthesis, bacterial N efficiency and enteric methane (CH4 ) production of 4 legumes containing different condensed tannins (CT) concentrations. Legumes were fermented in a 50:50 diet with orchardgrass (Dactylis glomerata L.): 1) Alfalfa (Medicago sativa L.; ALF no CT); 2) Birdsfoot trefoil (Lotus corniculatus L.; BFT, low CT); 3) Crown vetch [Securigera varia (L.); CV, moderate CT]; 4) Sericea lespedeza [Lespedeza cuneata (Dum. Cours.); SL, high CT]. Diets were randomly assigned to 4 fermentors in 4 periods in a 4 × 4 Latin square design, with 7 d for adaptation and 3 d for sample collection. Temperature, pH and CH4 concentrations were recorded. Effluent samples were analyzed for pH, VFA, and DM, OM, CP, NDF and ADF for determination of apparent (DM, OM, NDF and ADF) and true (DM and OM) nutrient digestibilities. Microbial protein synthesis and bacterial efficiency were estimated by analysis of N flows and purines. Forage samples were analyzed for DM, OM, CP, NDF, ADF, minerals and CT concentrations. Data were analyzed using the GLIMMIX procedure of SAS. The CT concentrations (g/kg DM) were 3, 21, 38 and 76 in ALF, BFT, CV and SL, respectively. Apparent and true DM and OM digestibilities were lower (P < 0.01) in SL than in ALF and BFT. Bacterial N efficiency per kg of truly digested DM and OM was lower (P = 0.05) in SL than in BFT and CV. The lowest (P < 0.001) CH4 production per unit of digestible nutrients was found in SL. There was a negative correlation (P < 0.001) between CT concentration and CH4 production. However, tradeoffs in ruminal fermentation (reduced nutrient digestibility, VFA concentration and bacterial N efficiency) must be considered when SL is used.